(Un)intended Consequences of a Mandatory Dividend Payout Regulation for Earnings Management: Evidence From a Natural Experiment. (October 2017) - Welker, Michael; Ye, Kangtao; Zhang, Ning
We examine the (un)intended consequences of a mandatory dividend payout regulation for firms' financial reporting choices using a natural experiment in China. Beginning in October 2008, China required firms desiring to raise new equity capital to maintain a cumulative dividend payout ratio of at least 30% over the past 3 years. We find that firms with a cumulative payout ratio from the prior year very close to but slightly lower than the mandated dividend threshold report lower discretionary accruals but do not increase dividends. In addition, this pattern is more pronounced in firms with greater cash flow deficits, firms with faster sales growth, and firms located in regions with lower bank development. We also find that the negative discretionary accruals are concentrated in firms with return on equity well in excess of another regulatory benchmark. In contrast, the only firms that increase dividends in response to the regulation are firms with a positive cumulative payout ratio far below the mandated threshold. Because dividend payout regulations have been suggested as a possible solution to agency problems, our results provide important policy feedback about the effectiveness of such regulations.